APPLICATION OF ANP AND TOPSIS TO SELECTION OF UNMANNED AERIAL VEHICLES (UAV) LAND-BASED LOCATIONS FOR SUPPORTING THE INDONESIAN NAVY MISSION - Helmi Amrullah; Yoyok Nurkaya; Rakam Rakam (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2022)
The Indonesian archipelagic sea lane which connects the Indian Ocean with the Pacific Ocean and East Asia withAustralia brings huge consequences to the efforts to implement security. Therefore, Indonesia needs facilities andinfrastructure to carry out the enforcement of state sovereignty while maintaining security in all areas of nationaljurisdiction. The naval battle strategy using aircraft as an extended sensor system has shown the ability that navalbattle tactics will be more effective in detecting the enemy. In carrying out the defense function, almost all defenseequipment owned by the Indonesian navy currently need the radar as a remote sensing system or as an earlywarning system. The strategic location of land base is needed in optimizing the current detection system. Theability of UAVs for security and defense at sea needs to be developed as an Integrated Fleet Weapon System(SSAT) to fulfill the functions of tactical reconnaissance and sea surveillance (Surveillance). The use of the UAVcan also increase strength and complement the need for maritime patrol aircraft (MPA), which so far has not beenmet quantitatively in covering all waters of Indonesia's national jurisdiction. The area of the Indonesianarchipelagic sea lane is in the working area of the First Fleet Command (Koarmada I). Where there are someLantamal and Lanal underneath. In order to optimize the placement of the ScanEagle UAV in the Indonesianarchipelagic sea lane region, it is very important to create a UAV location determination model using the ANP andTOPSIS methods. The first step is to develop criteria and sub-criteria for the Landbase location of the Landbase(UAV) in the Indonesian archipelagic sea lane region using the Analytical Network Process (ANP) method. Thenext step is to compile the criteria and sub-criteria for the location of the Landbase (UAV) in the Indonesianarchipelago sea lanes. The last step is to arrange the best priority location using the TOPSIS method. The resultsof determining the location of the ScanEagle UAV Landbase are expected to be used as input in formulating astrategy for projecting the future strength of the Indonesian navy.Keywords: UAV, SSAT, Surveillance, ScanEagle, ANP, TOPSIS